Study guide, chapters 1-15 for use with college accounting - Koerber, Kenneth A. (Homewood, IL. , Irwin, Inc., 1992)
"This student study guide is designed to assist you in your understanding of the terminology, concepts and principles that you have been introduced to in your first accounting course. This guide will help you review the concepts presented in each chapter. Reinforce the material so that you can develop an in-depth understanding of accounting. Improve your performance level on test and have fun while learning accounting! Accounting can be fun! Use the study guide as a supplement to your textbook and you will climb the steps to success quickly. "
English text.
Keywords: Accounting